Локально нильпотентные группы конечного неабелева секционного ранга - Дашкова, О.Ю. (Український математичний журнал, 1995)
Введено поняття неабелевого секційного рангу групи. Вивчаються неабелеві локально нільпотентні групи скінченного неабелевого секційного рангу і доводиться, що їх (спеціальний) ранг скінченний. We introduce the notion of non-Abelian sectional rank of a group and study locally nilpotent non-Abelian groups of finite non-Abelian sectional rank. It is proved that the (special) rank of these groups is finite.